2020
DOI: 10.3389/fcvm.2020.584987
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Features and Their Associations With Disease Severity and Mortality in Patients With COVID-19

Abstract: Background: Emerging studies have described and analyzed epidemiological, clinical, laboratory, and radiological features of COVID-19 patients. Yet, scarce information is available regarding the association of lipid profile features and disease severity and mortality.Methods: We conducted a prospective observational cohort study to investigate lipid profile features in patients with COVID-19. From 9 February to 4 April 2020, a total of 99 patients (31 critically ill and 20 severely ill) with confirmed COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 26 publications
5
66
1
4
Order By: Relevance
“…With recovery from COVID-19 infection the lipid levels return towards levels present prior to infection ( 28 , 29 , 30 , 42 , 43 ). As expected, the greater the severity of the illness the greater the reduction in LDL-C and/or HDL-C levels ( 29 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 42 , 44 , 45 ). LDL-C and HDL-C levels are inversely correlated with C-reactive protein (CRP) levels i.e., the higher the CRP levels the lower the LDL-C or HDL-C level ( 28 , 29 , 31 , 45 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinssupporting
confidence: 69%
See 1 more Smart Citation
“…With recovery from COVID-19 infection the lipid levels return towards levels present prior to infection ( 28 , 29 , 30 , 42 , 43 ). As expected, the greater the severity of the illness the greater the reduction in LDL-C and/or HDL-C levels ( 29 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 42 , 44 , 45 ). LDL-C and HDL-C levels are inversely correlated with C-reactive protein (CRP) levels i.e., the higher the CRP levels the lower the LDL-C or HDL-C level ( 28 , 29 , 31 , 45 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinssupporting
confidence: 69%
“…Low LDL-C and/or HDL-C levels at admission to the hospital predict an increased risk of developing a severe disease. Increased mortality was observed in patients with low total cholesterol, LDL-C, and/or HDL-C levels at admission to the hospital and in these very ill patient’s lipid levels continued to decline during the hospitalization ( 28 , 36 , 38 , 41 , 43 , 44 , 45 ). A single study reported that the time to develop a negative RT-PCR test for SARs-CoV-2 was increased in patients with low HDL-C levels ( 46 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinsmentioning
confidence: 99%
“…Hypertriglyceridemia induces endothelial dysfunctionality, causing COVID-19 patients to become more susceptible to complications related to cardiovascular diseases 14 . It was reported that TG levels signi cantly increased in COVID-19 patients with poor prognoses 15 .…”
Section: Discussionmentioning
confidence: 98%
“…A marked decrease in HDL-c concentrations during the acute phase response is well documented, however, the mechanisms underlying this decrease are not clearly de ned. Apolipoprotein-1 (ApoA-1), a major structural protein of HDL-c, reportedly decreased together with lower HDL-c when proin ammatory cytokines, such as interleukin-6 (IL-6) and CRP inhibited the activity of apolipoprotein synthesis enzymes 15,17 . Serum amyloid A (SAA)-enriched HDL displaced and decreased ApoA-1 levels and scavenged HDL more rapidly which was signi cantly higher in patients with a severe COVID-19 diagnosis 11,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation